2009
DOI: 10.2478/v10101-009-0018-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two kinds of aerobic training on body fat content and serum lipid profile in cadets

Abstract: Effects of two kinds of aerobic training on body fat content and serum lipid profile in cadets Study aim: To assess the effects of aerobic training on body fat content and serum lipid profile. Material and methods: A group of 45 male members of Brazilian Military Police Academy, aged 18 - 32 years, were subjected randomly assigned into 3 subgroups and to 12-week programmes: aerobic fatmax zone training (FG; n = 18), traditional military traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
1
0
3
Order By: Relevance
“…A atividade física aumenta o gasto energético, promove a utilização de gorduras e aumenta a oxidação de ácidos graxos, contribuindo para redução de peso e proteção do sistema cardiovascular (SPRIET, 2002). Os efeitos do exercício aeróbico sobre a redução de peso variam entre os indivíduos, pois são influenciados por uma série de fatores, como ambientais, intensidade do exercício, massa muscular, nível de hormônios circulantes, idade e gênero (SOUZA, 2009).…”
unclassified
“…A atividade física aumenta o gasto energético, promove a utilização de gorduras e aumenta a oxidação de ácidos graxos, contribuindo para redução de peso e proteção do sistema cardiovascular (SPRIET, 2002). Os efeitos do exercício aeróbico sobre a redução de peso variam entre os indivíduos, pois são influenciados por uma série de fatores, como ambientais, intensidade do exercício, massa muscular, nível de hormônios circulantes, idade e gênero (SOUZA, 2009).…”
unclassified
“…Meta-analyses have concluded that aerobic training is effective in reducing clinical blood pressure in the general population as well as in hypertensive patients [6]. Aerobic exercise is more effective than other exercises in reducing body fat percentage [7]. Aerobic exercise reduces acyl-CoA synthesis and markedly acyl-CoA synthesis mRNA levels, lipoprotein lipase, and GLUT4 in adipose tissue.…”
mentioning
confidence: 99%
“…Μειώνοντας λοιπόν κανείς το σωματικό του λίπος και το σωματικό βάρος προστατεύει κυρίως το καρδιοαγγειακό του σύστημα (Berg et al, 2002). Το ACSM και η AHA συνιστά στους ενήλικες άνδρες τη φυσική δραστηριότητα τουλάχιστον 2 φορές την εβδομάδα (Haskell et al, 2007 (Malavolti et al, 2008;Souza e Silva et al, 2009;Mikkola et al, 2012;Margolis et al, 2012) και αύξηση της άλιπης σωματικής μάζας (deAvila, deBarros Lima, Pascoa & Tessutti, 2003) ιδίως σε λιποβαρείς στρατιώτες. Σε αντίθεση με τους παχύσαρκους που παρουσίασαν μείωση του σωματικού βάρους και μείωση του ποσοστού λίπους άλλα δεν παρουσίασαν όμως σημαντικές αλλαγές στην άλιπη σωματική μάζα (Mikkola et al, 2009).…”
Section: επίδραση της προπόνησης μυϊκής ενδυνάμωσης στη σύσταση σώματοςunclassified
“…Από την ανασκόπηση της βιβλιογραφίας φαίνεται ότι βελτίωση στην VO 2 max παρουσιάζουν κυρίως έρευνες που περιλαμβάνουν κυκλική άσκηση με αντιστάσεις ή συνδυασμό με αερόβια άσκηση (de Souza e Silva et al, 2009;Dyrstad et al, 2006;Heinrich et al, 2012;Westcott et al, 2007). Πρωτόκολλο αερόβιας άσκησης με κυκλικό πρόγραμμα που είχε έμφαση στην δύναμη για 12 εβδομάδες έδειξε σημαντική βελτίωση στον δρόμο 1,5 μιλίου (Westcott et al, 2007).…”
Section: άσκηση με αντιστάσεις και αερόβια αντοχήunclassified